Analisis Pengembangan Karier Pegawai Negeri Sipil Berdasarkan Undang – Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara di Badan Kepegawaian Daerah Provinsi Jawa Tengah - Rostanti, Linda Felecia; Yuniningsih, Tri; Djumiarti, Titik (Journal of Public Policy and Management Review, 2016)
This study attempts to analyze and describe the implementation of career development based on the Civil Servants Regulation Number 5 Year 2014 about state civil apparatus in Human Resources Agency Provincial Government Of Central Java This research use descriptive research with a qualitative approach. The focus of this study include four (4) dimensions of qualification, competence dimensions, dimensions of performance appraisal, as well as the dimensions of the needs of government agencies. The results show that human resources agency provincial government central java in general has conducted development career with well even though in its implementation still often referred to previous regulation, and consequently a shortage of various things study. Advice that provided is the development of career in Human Resources Agency Provincial Government Central Java needs to be improved and fully reference to civil regulation state apparatus that can be used as a reference for all agencies that exist in the environment of Central Java Province.